Applying Theory of Mind to Multi-agent Systems: A Systematic Review - Rocha, Michele; Silva, Heitor Henrique da; Morales, Analúcia Schiaffino; Sarkadi, Stefan; Panisson, Alison R. (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2023)
Life in society requires constant communication and coordination. These abilities are efficiently achieved through sophisticated cognitive processes in which individuals are able to reason about the mental attitudes and actions of others. This ability is known as Theory of Mind. Inspired by human intelligence, the field of Artificial Intelligence aims to reproduce these sophisticated cognitive processes in intelligent software agents. In the field of multi-agent systems, intelligent agents are defined not only to execute reasoning cycles inspired by human reasoning but also to work similarly to human society, including aspects of communication, coordination, and organisation. Consequently, it is essential to explore the use of these sophisticated cognitive processes, such as Theory of Mind, in intelligent agents and multi-agent systems. In this paper, we conducted a literature review on how Theory of Mind has been applied to multi-agent systems, and summarise the contributions in this field.